Mass-Stiffness Combined Perturbation Method for Mode Shape Monitoring of Bridge Structures. (6th November 2019) - Zhang, Liye; Xia, Ye; Lozano-Galant, Jose A.; Sun, Limin
Abstract : Identification of the mode shapes through monitoring is one of the key problems in damage diagnosis based on modal parameters especially for damaged structures. In order to obtain mode shapes of damaged structures easily and accurately, the mass-stiffness combined perturbation (MSCP) method is proposed in this paper. To do so, the relationship between the stiffness perturbation mode shapes of damaged and intact structures is firstly derived and established. Then, the principle of similar frequency is applied to optimize the objective function of the most suitable mass perturbation model. Both numerical analyses and experimental tests on simple and complex structures demonstrate that the proposed MSCP method achieves higher precision than traditional mode shape identification methods. The additional advantages of the MSCP method include (i) lower requirement on the frequency analysis of only damaged structures and (ii) higher effectiveness for minor damage scenarios. In fact, the lower the damage, the higher the precision achieved by the MSCP method. As illustrated in the paper, the proposed technique has excellent applications in mode shapes identification and structural health monitoring.